2016
DOI: 10.1111/imb.12275
|View full text |Cite
|
Sign up to set email alerts
|

Identification and initial characterization of matrix metalloproteinases in the yellow fever mosquito, Aedes aegypti

Abstract: Aedes aegypti is a major vector for arboviruses such as dengue, chikungunya, and Zika viruses. During acquisition of a viremic bloodmeal, an arbovirus infects mosquito midgut cells before disseminating to secondary tissues, including the salivary glands. Once virus is released into the salivary ducts it can be transmitted to another vertebrate host. The midgut is surrounded by a basal lamina (BL) in the extracellular matrix, consisting of a proteinaceous mesh composed of collagen IV and laminin. BL pore size e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…The zymogen (50 kDa) and the active form of AeMMP1 (37 kDa) lacking its propeptide domain were highly expressed between 3 and 24 h pbm ( Fig 3A ) concurring with the time period during which collagen IV was less detectable ( Fig 2A ). Similar to what we had recently observed [ 27 ], the catalytically active form of AeMMP1 was barely detectable in midguts between 36 and 72 h pbm ( Fig 3A ). Typically, most of the bloodmeal has been digested by 48 h post-acquisition allowing the midgut tissue to contract and the BL to rebuild.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The zymogen (50 kDa) and the active form of AeMMP1 (37 kDa) lacking its propeptide domain were highly expressed between 3 and 24 h pbm ( Fig 3A ) concurring with the time period during which collagen IV was less detectable ( Fig 2A ). Similar to what we had recently observed [ 27 ], the catalytically active form of AeMMP1 was barely detectable in midguts between 36 and 72 h pbm ( Fig 3A ). Typically, most of the bloodmeal has been digested by 48 h post-acquisition allowing the midgut tissue to contract and the BL to rebuild.…”
Section: Resultssupporting
confidence: 90%
“…Recently, we showed that two of the nine MMPs of Ae . aegypti , AeMMP1 and AeMMP2, were active in midgut tissue and responded to the presence of a bloodmeal [ 27 ]. AeMMP2 was associated with tracheal cells surrounding the midgut, whereas AeMMP1 was highly expressed in epithelial cells, the site at which CHIKV infection occurs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations